Prevalence of meditation-related adverse effects in a population-based sample in the United States - Goldberg, Simon B.; Lam, Sin U.; Britton, Willoughby B.; Davidson, Richard J. (Psychotherapy research, 2022)
Meditation practice and meditation-based psychotherapies have become increasingly popular. Although psychological benefits associated with meditation are well-documented, potential risks are unclear. We conducted a population-based survey to evaluate the occurrence of a broad range of meditation-related adverse effects (MRAE). Nine hundred and fifty three participants completed our screening survey, 470 endorsed lifetime exposure to meditation practice, and 434 completed a follow-up survey assessing MRAE (92.3% response rate). A higher proportion than hypothesized reported occurrence of MRAE (general item = 32.3%, 1+ specific item = 50.0%) and MRAE duration ≥1 month (10.4%). Anxiety, traumatic re-experiencing, and emotional sensitivity were the most common MRAE. Some degree of functional impairment was reported by 10.6% of participants, with impairment lasting ≥1 month for 1.2%. Childhood adversity was associated with elevated risk for MRAE. Participants reporting MRAE were equally glad to have practiced meditation as those not reporting MRAE. Additional correlates of MRAE were identified in exploratory analyses. MRAE are common, even in a sample with relatively modest amounts of experience. Identifying individuals at elevated risk for MRAE, being transparent and realistic about the possible range of effects, and increasing trauma-sensitivity are warranted to maximize benefits and minimize risks of meditation.